Peran Hukum Dalam Melindungi Anak Dari Kekerasan Seksual Di Lingkungan Sekolah - Trenada, Tarisa Febby (Jurnal JURISTIC, 2024)
The objective of this article is to address the issue of protecting children from sexually violent crimes within school environments. While educational institutions are meant to provide a sense of security and comfort akin to that of a family environment, the unfortunate reality is that immoral crimes still occur within school premises. The violation of children's decency is not solely an educational concern but also a matter governed by a country's national laws. Indonesia, being a country that upholds the rule of law, places great emphasis on the protection and prevention of sexual violence against children in schools, as it is crucial in safeguarding their rights. Our research took the form of legal research utilizing a qualitative method with descriptive analysis. Data was gathered through interviews and observations conducted on the relevant issues within the field. The study concluded that discussions or actions related to sexual matters within the school environment can significantly contribute to making schools unsafe for students. Therefore, the existence of provisions regarding criminal acts for perpetrators who engage in sexually inappropriate behavior, as stipulated in current Indonesian regulations, may serve to minimize such incidents from occurring.